WHAT AND WHY DO STUDENTS WRITE IN A BIOLOGY LABORATORY PRACTICE AT SECONDARY SCHOOL? (2015)
Writing plays a central role in the comprehension of scientific concepts; however, at school it is frequently used as an evaluation resource or just for recording data. Taking this into account, we were interested in investigating the role of writing in class and the students’ perceptions about it. In this article, we characterize the manuscripts that fifth year students wrote and the points of view about writing they exposed, in a private secondary school in Córdoba, Argentina. We analyzed the students’ drafts and final reports from different perspectives and we investigated through a questionnaire how students value the writing task and practical classes. The gathered results showed that students understand practical classes as any other learning opportunity contributing to Biology comprehension through conceptual and procedural tools. Besides, up to a certain extent, students recognized the epistemic potential of writing. In spite of these positive results, there were not relevant changes between the drafts and the final written productions, and the reports included predominantly narrative and explicative instead of argumentative sequences.